2014
DOI: 10.1002/jor.22586
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the anterior–posterior rotator cuff force balance alters joint function and leads to joint damage in a rat model

Abstract: The rotator cuff assists in shoulder movement and provides dynamic stability to the glenohumeral joint. Specifically, the anterior–posterior (AP) force balance, provided by the subscapularis anteriorly and the infraspinatus and teres minor posteriorly, is critical for joint stability and concentric rotation of the humeral head on the glenoid. However, limited understanding exists of the consequences associated with disruption of the AP force balance (due to tears of both the supraspinatus and infraspinatus ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 25 publications
2
34
0
3
Order By: Relevance
“…For example, tendon impingement is a leading cause of rotator cuff tendinopathy. Additionally, rotator cuff tears can cause a force imbalance in the shoulder joint, which results in tendinopathy in adjacent rotator cuff tendons [9799]. Taken together, these data suggest that overuse and abnormal loading may disrupt the homeostatic balance between synthesis and degradation, creating an overall catabolic response and development of disease.…”
Section: Case Study 1: the Extracellular Matrix In The Tendonmentioning
confidence: 99%
“…For example, tendon impingement is a leading cause of rotator cuff tendinopathy. Additionally, rotator cuff tears can cause a force imbalance in the shoulder joint, which results in tendinopathy in adjacent rotator cuff tendons [9799]. Taken together, these data suggest that overuse and abnormal loading may disrupt the homeostatic balance between synthesis and degradation, creating an overall catabolic response and development of disease.…”
Section: Case Study 1: the Extracellular Matrix In The Tendonmentioning
confidence: 99%
“…In study #1 (Reuther et al, 2014a), animals underwent unilateral detachment of the supraspinatus only (SO) or supraspinatus and infraspinatus (SI) rotator cuff tendons, and ambulatory measurements were collected up to 8 weeks post-operatively. To create a more general model, data from the SO and SI groups were combined and used for the correlation and regression analysis in the current study as significant differences between these groups were observed in shoulder function (as measured by kinetic gait parameters), as well as tendon and cartilage mechanical and histological properties.…”
Section: Methodsmentioning
confidence: 99%
“…Overuse activity was modeled as stated in our previous publications. 18, 24 Initially, rats in overuse groups underwent a 2-week treadmill training period to acclimate them to running at the desired speed and for the desired duration. All groups then underwent unilateral surgical transection (or sham transection) of the spinal accessory and long thoracic nerves, resulting in denervation of the trapezius and serratus anterior muscles, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…18 Briefly, stain lines, for local optical strain measurements, were placed on the biceps and supraspinatus tendons, dividing the insertion and mid-substance regions. The scapula and humerus were embedded using polymethymethacrylate (PMMA) and secured in a custom testing fixture.…”
Section: Methodsmentioning
confidence: 99%